Comparative Analysis of the Crime of Sexual Abuse Against Children Based on Law Number 35 of 2014 concerning Child Protection and Qanun Aceh Number 6 of 2014 concerning Jinayah - Bagus Pribadi; Riza Zarzani (International Journal of Society and Law, 2024)
This research discusses the crime of sexual abuse of children, which is a criminal act and a violation of human rights. Sexual harassment is not only an individual problem, but also a social problem that affects women, children, and even men. This study aims to analyze the comparison between Law Number 35 of 2014 concerning Child Protection and Qanun Aceh Number 6 of 2014 concerning Jinayah in handling the crime of sexual abuse against children. By analyzing the differences in Indonesia's positive law and Islamic sharia in Aceh, this study emphasizes the importance of preventing and enforcing the law against sexual abusers, as well as protecting children from physical and psychological violence.